(untitled) (Encuentros, 2020)
This investigation of the Buena Vista II neighborhood of Villa del Rosario-Norte de Santander, characterized by its displaced population victim of the Colombian internal armed conflict. It is developed from a documentary approach that contextualizes the consequences of the conflict and conceptually defines quality of life. It presents a mixed methodology; qualitative, which recognizes the dynamics and conditions of habitability and; quantitative, which performs a population characterization from the social, economic and environmental dimensions that identifies the quality of life needs of the inhabitants. This research allows us to establish the impact of architecture on the quality of life of the populations victims of the Colombian armed conflict, as an element that determines repair and rehabilitation processes in the context of the post-conflict.